High CD34 surface expression in BCP‐ALL predicts poor induction therapy response and is associated with altered expression of genes related to cell migration and adhesion. Issue 10 (7th April 2022) - Modvig, Signe; Wernersson, Rasmus; Øbro, Nina Friesgaard; Olsen, Lars Rønn; Christensen, Claus; Rosthøj, Susanne; Degn, Matilda; Jürgensen, Gitte Wullf; Madsen, Hans O.; Albertsen, Birgitte Klug; Wehner, Peder Skov; Rosthøj, Steen; et al.
Abstract : Minimal residual disease (MRD) constitutes the most important prognostic factor in B‐cell precursor acute lymphoblastic leukemia (BCP‐ALL). Flow cytometry is widely used in MRD assessment, yet little is known regarding the effect of different immunophenotypic subsets on outcome. In this study of 200 BCP‐ALL patients, we found that a CD34‐positive, CD38 dim‐positive, nTdT dim‐positive immunophenotype on the leukemic blasts was associated with poor induction therapy response and predicted an MRD level at the end of induction therapy (EOI) of ≥ 0.001. CD34 expression was strongly and positively associated with EOI MRD, whereas CD34‐negative patients had a low relapse risk. Further, CD34 expression increased from diagnosis to relapse. CD34 is a stemness‐associated cell‐surface molecule, possibly involved in cell adhesion/migration or survival. Accordingly, genes associated with stemness were overrepresented among the most upregulated genes in CD34‐positive leukemias, and protein–protein interaction networks showed an overrepresentation of genes associated with cell migration, cell adhesion, and negative regulation of apoptosis. The present work is the first to demonstrate a CD34‐negative immunophenotype as a good prognostic factor in ALL, whereas high CD34 expression is associated with poor therapy response and an altered gene expression profile reminiscent of migrating cancer stem‐like cells. Abstract : This study reports that a leukemic cell immunophenotype with high CD34 surface expression predicts poor induction therapy response in B‐cell precursor acute lymphoblastic leukemia. Moreover, blast CD34 expression increases from diagnosis to relapse. Protein–protein interaction network analysis and gene set enrichment analysis show increased expression of genes associated with stemness, cell adhesion, cell migration, and cell survival in CD34‐positive cases.